Reseña de Sandman: Obertura de Neil Gaiman, J.H. Williams III y Dave Stewart - Vilches, Gerardo (CuCo, Cuadernos de cómic, 2016)
Reseña de Sandman: Obertura de Neil Gaiman, J.H. Williams III y Dave Stewart